NEW RECORD OF PARASESARMA RAOULI RAHAYU AND NG, 2009 (CRUSTASEA: BRACHYURA: SESARMIDAE) FROM THE RIAU ARCHIPELAGO, INDONESIA - Widyastuti, Ernawati; Rahayu, Dwi Listyo (Marine Research in Indonesia, 2016)
A specimen of Parasesarma raouli (Crustacea: Brachyura: Sesarmidae) was collected from the mangrove area of Pulau Berang, Lingga, Riau Archipelago, Indonesia in Oktober 2014. This species previously was known only from Johor strait, Peninsular Malaysia. Its color in life is recorded for the first time.